Cytotoxic activity of effector T cells against cholangiocarcinoma is enhanced by self-differentiated monocyte-derived dendritic cells - Aussara Panya (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Cholangiocarcinoma (CCA) is a cancer of the bile ducts that is associated with poor prognosis and poor treatment outcome. Approximately one-third of CCA patients can undergo surgery, but the recurrence rate is high and chemotherapy often cannot satisfactorily prolong survival. Cellular immunotherapy based on adoptive T-cell transfer is a potential treatment for CCA; however, the development of this technology and the search for an appropriate tumor-associated antigen are still ongoing. To enhance the cytotoxic activity of effector T cells against CCA, we developed self-differentiated monocyte-derived dendritic cells (SD-DC) presenting cAMP-dependent protein kinase type I-alpha regulatory subunit (PRKAR1A), which is an overexpressed protein that plays a role in the regulation of tumor growth to activate T cells for CCA cell killing. Dendritic cells (DCs) transduced with lentivirus harboring tri-cistronic cDNA sequences (SD-DC-PR) could produce granulocyte–macrophage colony-stimulating factor, interleukin-4, and PRKAR1A. SD-DC showed similar phenotypes to those of DCs derived by conventional method. Autologous effector T cells (CD3+, CD8+) activated by SD-DC-PR exhibited greater cytotoxic activity against CCA than those activated by conventionally-derived DCs. Effector T cells activated by SD-DC-PR killed 60% of CCA cells at an effector-to-target ratio of 15:1, which is approximately twofold greater than the cell killing performance of those stimulated with control DC. The cytotoxic activities of effector T cells activated by SD-DC-PR against CCA cells were significantly associated with the expression levels of PRKR1A in CCA cells. This finding that SD-DC-PR effectively stimulated autologous effector T cells to kill CCA cells may help to accelerate the development of novel therapies for treating CCA.